Prevalence of normal weight central obesity among Thai healthcare providers and their association with CVD risk: A cross-sectional study - Lakkana Thaikruea (2018)
© The Author(s) 2016. This study aims to determine the prevalence of health personnel with normal weight central obesity and to investigate whether this group had higher cardiovascular disease (CVD) risk factors than those of the people with normal weight and without central obesity. A waist-to-height ratio was calculated as waist circumference (at umbilical level) in cm divided by height in cm. The central obesity cut-off level was 0.5. The body mass index was calculated as weight in kg divided by height in meters squared. The obesity cut-off level was 25 kg/m 2. The prevalence of health personnel with normal weight central obesity was 15.4% (499 out of 3235). When compare this group to 1787 health personnel who had normal weight and without central obesity, they were 2.03 times (95% CI of adjusted OR; 1.62 to 2.54) more likely to have at least one CVD factor. The waist-to-height ratio cut-off value of 0.5 can be used as a self-assessment tool for central obesity without the need for a standard measuring tape. It is feasible to be implemented in screening or self-monitoring for the general population.